A Multidisciplinary Approach to Diabetes Management: The Roles of Nursing, Social Workers, and Pharmacists - Ali Ahmed Mohammed ALkathiri; Saeed Mohammed Alkathere; Mesfer Saleh Ahmed Alshomrani; Mohammed Ahmed Al Shomrani; Mohmmed Shalan Alalyani; Gdeer Saeed Ayed Alsalmi; Hassan Awadh Mohammad Alqarni; Saleh Mohammad mousa Alqarni (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Diabetes mellitus presents both complexity and extended duration thus needing detailed integrated management protocols. The disease impacts millions of people throughout the globe by causing an array of medical conditions including cardiovascular problems and kidney breakdown and nerve damage and impaired vision. The management of diabetes goes beyond therapeutic interventions to involve medical and healthcare delivery as well as social aspects of care together with psychological aspects. Effective disease management combined with better patient results can only be achieved through a multidisciplinary healthcare team which includes nurses, social workers and pharmacists. Aim of work: Toexplore the critical roles of nurses, social workers, and pharmacists in diabetes management, highlighting their contributions to patient education, psychosocial support, and medication management Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Multidisciplinary, Approach, Diabetes, Management, Roles, Nursing, Social Workers, and Pharmacists. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:In conclusion, multi-disciplinary diabetes care presents opportunities for better patient results but implementation needs careful attention to various obstacles for successful outcomes. Several key factors including healthcare professional coordination and resource availability and patient participation and mental health incorporation and ongoing staff development and health system policies determine the success of collaborative care approaches in effective medicine. The successful implementation of patient-centered diabetes management requires strong collaborative action among healthcare institutions and policymakers and medical professionals to create durable solutions which will enhance broad diabetes management practices.